Perkembangan Dakwah Era Teknologi dan Dampaknya - Sarkawi, Sarkawi (Journal of Da'wah, 2023)
Da’wah is a command of Allah, da'wah must also continue and be conveyed to the people, the implementation of da'wah from time to time continues to experience changes and developments, challenges and opportunities for da'wah also become an inseparable part along with the times, the world of technology is developing increasingly sophisticated and rapidly provide space and a very significant impact on the development of Da'wah, but on the other hand, the values ​​of Da'wah sometimes become hampered from being able to be applied perfectly. This article discusses the development of Da'wah in the Technology era and its development which aims to find out the development of Da'wah in the technological era and the impact caused by using research methods, literature searches and analysis both from literature and observations, from this discussion it is concluded that Technological Developments provide convenience in the implementation of Da'wah activities, and provide an open space so that da'wah can be conveyed quickly and precisely and can be more easily, either through writing, video and so on, but it is undeniable that freedom in the world of technology provides opportunities for people who are not responsible for conveying information and or as if the study of da'wah but sometimes misguided and misleading, this is because users sometimes have started to be less careful about the sources they get